2018
DOI: 10.21037/jss.2018.12.02
|View full text |Cite
|
Sign up to set email alerts
|

Objective monitoring of activity and Gait Velocity using wearable accelerometer following lumbar microdiscectomy to detect recurrent disc herniation

Abstract: We report a case of a 39-year-old male with sciatica who underwent an L5/S1 microdiscectomy with objective physical activity measurements performed preoperatively and continually postoperatively up to 3-month using wireless accelerometer technology linked to the surgical practice; collecting distance travelled, daily step count (DSC) and Gait Velocity (GV). Preoperative, the patient was walking with a GV of 0.97 m/s and a DSC of less than 2,500. After the first month following surgery, the patient had increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 21 publications
1
21
0
Order By: Relevance
“…The current study findings showed a significant decrease in disability levels in the second and third months in the intervention group compared with the control group. This finding is consistent with previous study results (Can et al, 2010; Jakobsson et al, 2019; Mobbs et al, 2018; Phan & Mobbs, 2016). Whereas some authors reported that exercise programs starting 4 to 6 weeks after surgery caused rapid decreases in pain and disability (Ostelo et al, 2009), other authors reported that although the effects of early activity on pain may be felt sooner, the effects on functional capacity would emerge later (Ozkara et al, 2015).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The current study findings showed a significant decrease in disability levels in the second and third months in the intervention group compared with the control group. This finding is consistent with previous study results (Can et al, 2010; Jakobsson et al, 2019; Mobbs et al, 2018; Phan & Mobbs, 2016). Whereas some authors reported that exercise programs starting 4 to 6 weeks after surgery caused rapid decreases in pain and disability (Ostelo et al, 2009), other authors reported that although the effects of early activity on pain may be felt sooner, the effects on functional capacity would emerge later (Ozkara et al, 2015).…”
Section: Discussionsupporting
confidence: 93%
“…Pain and disability can be prevented in the early post‐operative period after lumbar hernia surgery through appropriate care and rehabilitation (den Boer et al, 2006). However, the number of studies in the literature on the effectiveness of walking after LDH surgery and its use as an intervention strategy is limited (Mobbs et al, 2016, 2018; Phan & Mobbs, 2016). In light of this information, the aim of this study was to evaluate the effect of pedometer‐supported walking and telemonitoring on patients' pain, disability and quality of life after LDH surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Improved Follow-Up mHealth apps offer a cost-effective way to safely allow earlier discharge while maintaining close follow-up with patients postoperatively (19,20). It can save time for care providers and patients and reduce unnecessary transfers.…”
Section: Behavior and Activity Modificationmentioning
confidence: 99%
“…Khodedadah and Eisenstein (1993) established a correlation between gait improvement, particularly gait velocity, in patients with low back pain after lumbar fusion surgery [9]. In recent years, gait analysis has been increasingly utilised for assessing patient outcomes for various other spinal pathologies [10]. Patients with LSS have larger gait variability pre-operatively compared to post-operatively, and when compared to healthy subjects [11, 12].…”
Section: Introductionmentioning
confidence: 99%